Severity of postoperative cardiac surgery patients: na evolution analysis according to TISS-28 (Revista Latino-Americana de Enfermagem, 2010)
This study verified the daily TISS-28 score in the postoperative period of cardiac surgery at a cardiology intensive care unit. This cohort study included 55 postoperative cardiac surgery patients, who were sent to the intensive care unit to recover. Data were collected from patients records with daily application of the TISS-28. The obtained data revealed that the average age of the population was 61.47 years ± 12.12 years, 78.2% were male, 51.43% underwent valve repair surgery and 48.57% myocardial revascularization surgery. The severity index in the immediate postoperative period was 41.33 ± 5.01. The follow-up of patients using the TISS-28 evidenced a significant decrease in the index values up to the patients discharge, averaging at 13.19 ± 2.59. The results indicate that immediate postoperative cardiac surgery patients are in severe conditions, hemodynamically unstable and classified in class III according to the TISS-28, though scores gradually decrease over time.